HUBUNGAN STRES DENGAN KEJADIAN TIMBULNYA ACNE VULGARIS PADA SISWA DI SMP NEGERI 2 KOTA BANDA ACEH - Firnanda, Ryan; Masthura, Syarifah; Mulyatina, Mulyatina (Coping: Community of Publishing in Nursing; Vol 10 No 4 (2022): Agustus 2022DO - 10.24843/coping.2022.v10.i04.p02, 2022)
Stress can not only affect a person’s psyche but can also affect in term of pathophysiology. Stress causes one of the skin disease that are often a problem for adolescents and adults, namely acne vulgaris. This study aims to determine the relationship of stress with the incidence of acne vulgaris. This study used a correlational descriptive by incorporating the cross-sectional design. The total sample was 81 respondents. The measuring instrument used is a questionnaire and GAGS (Global Acne Grading System) observation sheet. Validity test using the item-total correlation, the results of the validity value r > 0,444 and declared valid. The reliability test obtained the results of the cronbach alpha value of 0,60, so it can be concluded that the instrument is declared reliable. Bivariate test showed that there was correlation between stress and the incidence of acne vulgaris among students in SMP Negeri 2 Banda Aceh 2019 with p-value = 0,001. Moderate acne vulgaris mostly occurs in students who experience stress, while mild acne vulgaris occurs in students who do not experience stress.